A Review on Gold Nanoparticles (GNPs) and their Advancement in Cancer Therapy - Shabbir Hussain; Muhammad Amjad (International Journal of Nanomaterials, Nanotechnology and Nanomedicine - Peertechz Publications, 2021)
There are approximately 18 million cancer cases have been observed per year worldwide according to Global cancer therapy (GLOBOCAN). Chemotherapy, radiotherapy and surgery have been mostly used for cancer therapy. The maximum tolerated dose is currently being used to cure patients. The incorporated advancement of modern nanoparticle-based techniques will be important to find one of the main issues in both radiotherapy and chemotherapy: normal tissue toxicity. The Gold Nanoparticle (GNP) based systems are very helpful to further improve chemotherapy by controlled releases of chemotherapeutics, but local radiotherapy dose can be improved through targeting the GNPs to the tumor. Over 20 nanotechnology-based therapeutic products have been authorized for clinical use in the past two decades. The main purpose of this review article is to understand how we can accelerate the clinical use of GNP-based therapeutic system to reduce normal tissue toxicity while increasing the worth of the treatment. Nanomedicines will change future cancer treatment methods in a better way that has minimum side effects.